Application of the Double Diamond Method in the UI/UX Website Redesign to Improve User Engagement, Experience, and Satisfaction of ABC Housing - Syach, Irzha Nabhan; Arifah, Ika Diyah Candra; Kroft, Kroen van der (Journal of Digital Business and Innovation Management, 2025)
This study aims to implement the Double Diamond method in the redesign process of the UI/UX for the ABC Housing website located in Madura. The objective is to improve user engagement, experience, and satisfaction by applying a structured, user-centered design approach. The redesign process followed four key stages: Discover, Define, Develop, and Deliver, beginning with user needs analysis and culminating in the development of a high-fidelity prototype. To evaluate the effectiveness of the new design, the System Usability Scale (SUS) was employed, involving feedback from six respondents. The findings demonstrate that the redesigned website significantly enhanced key usability aspects, particularly navigation ease, visual attractiveness, and the overall user experience. These improvements suggest that the new interface aligns more closely with user expectations and behaviors, thereby increasing the likelihood of user satisfaction and sustained engagement. As a result, the redesigned platform is expected to attract greater interest and foster trust among prospective buyers. This, in turn, supports the company’s broader digital marketing strategy by positioning the website as a more effective tool for communication, promotion, and customer conversion. The study underscores the value of applying iterative design methodologies like Double Diamond in creating impactful digital solutions.